Algorithms to live by : the computer science of human decisions - Christian, Brian; Griffiths, Tom. (London: william Collins, 2017)
A fascinating exploration of how computer algorithms can be applied to everyday lives, helping to solve common decision-making problems and illuminate the workings of the human mind.
Title from container.
Performed by Brian Christian.
Keywords: Human behavior -- Mathematical models; Problem solving -- Mathematics; Computer simulation; Computer algorithms; Computer algorithms; Computer simulation; Human behavior -- Mathematical models; Problem solving -- Mathematics; Audiobooks; Audiobooks